Transversus Abdominis Plane (TAP) Steroid Block for Chronic Abdominal Pain Caused by Chronic Postoperative Pain - Hamdi, Tasrif (CoinReads Media Prima, 2023)
Introduction: Various factors including surgical, psychological, amount of acute pain relief have been proposed as risk factors for developing CPSP. Different treatment modalities like nerve and plane blocks, psychiatric counselling have been described to counter this pain. Case: The patient was a 30-year-old female with complaints of severe pain in the right lower quadrant of the abdomen and found a surgical scar with hyperalgesia and a history of open appendicectomy surgery, two times section caesarean section surgery. The patient experienced pain after section caesarean section surgery 6 months ago. Because the pain was also felt in the right hypochondrium, the patient was unable to move his body, unable to sit and stand. The patient was diagnosed as a case of chronic post surgical pain syndrome (CPSP). We performed transversus abdominis plane block (TAP) with ultrasound guidance and lidocaine 15 ml combined with 40mg methylprednisolone. VAS scores showed significant improvement from 8/10 and 2/10 during the 10-day follow-up. We conclude that ultrasound-guided TAP block can be a treatment option for CPSP cases. Conclusion: Chronic post surgical pain (CPSP) is a definite clinical entity after laparatomy. We report a successful management of such a case with ultrasound guided transversus abdominis plane block. The patient had very significant pain relief after procedure follow up continue until today without any side effects.